Performance features in clinical skills assessment: Linguistic and cultural factors in the Membership of the Royal College of General Practitioners examination - Roberts, Celia; Atkins, Sarah; Hawthorne, Kamila (King's College London with The University of Nottingham, 2014)
This book is based on research looking at performance in clinical skills assessment from a linguistic and cultural perspective, with a view to understanding why there are such differential pass rates and giving suggestions on how this issue can be tackled. It is both a research report and a guide to the sociolinguistic methodology used. While the findings are based on a research project in partnership with the Royal College of General Practitioners, they are applicable to many other medical settings where standardised examinations of simulated consultations are used. More widely, this research addresses a central paradox in institutional life – how to balance validity in assessments and be fair to a diverse group of candidates in an increasingly diverse society, while maintaining reliability with standardised and universal marking criteria.